Teacher Labor Market Policy and the Theory of the Second Best - Michael Bates; Michael Dinerstein; Andrew C Johnston; Isaac Sorkin (The Quarterly Journal of Economics, 2025)
Abstract We estimate a matching model of teachers and elementary schools with rich data on teachers' applications and principals' ratings from a large, urban district in North Carolina. Both teachers’ and principals’ preferences deviate from those that would maximize the achievement of economically disadvantaged students: teachers prefer schools with fewer disadvantaged students, and principals' ratings are weakly related to teacher effectiveness. In equilibrium, these two deviations combine to produce a surprisingly equitable current allocation, where teacher quality is balanced across advantaged and disadvantaged students. To close achievement gaps, policies that address deviations on one side alone are ineffective or harmful, while policies that address both could substantially increase the achievement of disadvantaged students.